2021
DOI: 10.3390/math9172170
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Tax Compliance in the EU: VECM and SEM

Abstract: Tax compliance is an important indicator for the proper functioning of the tax authority, influencing the budget revenue level. In this study, a Vector Error Correction Model (VECM) analysis was developed to identify the long-term relationships between the compliance in individual income taxation (taxpayer’s behavior), public trust in politicians (trust in authorities), and rule of law (power of the authorities), using unbalanced panel data for the European Union (EU28) during the 2007–2017 period. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Kepatuhan pajak ini dianggap sebagai kemampuan dari Wajib Pajak untuk membayarkan pajak mereka kepada negara (Oladipo et al, 2022). Kepatuhan pajak ini penting untuk meningkatkan penerimaan anggaran negara, yang nantinya digunakan untuk keperluan program-program pemerintah (Surugiu et al, 2021). Sampai saat ini kepatuhan pajak masih menjadi masalah penting yang diperhatikan oleh negara, khususnya pada negara berkembang, karena tingkat kepatuhan pajak yang masih tergolong rendah (Damayanti et al, 2021).…”
Section: Pendahuluanunclassified
“…Kepatuhan pajak ini dianggap sebagai kemampuan dari Wajib Pajak untuk membayarkan pajak mereka kepada negara (Oladipo et al, 2022). Kepatuhan pajak ini penting untuk meningkatkan penerimaan anggaran negara, yang nantinya digunakan untuk keperluan program-program pemerintah (Surugiu et al, 2021). Sampai saat ini kepatuhan pajak masih menjadi masalah penting yang diperhatikan oleh negara, khususnya pada negara berkembang, karena tingkat kepatuhan pajak yang masih tergolong rendah (Damayanti et al, 2021).…”
Section: Pendahuluanunclassified
“…Šimović (2018) highlights that the growth of budget deficits was a result of the inadequate adjustment of public expenditures and raising interests on the public debt, causing losses Economies 2024, 12, 131 2 of 15 in tax revenues. Therefore, governments have an expanding need for financial resources (Surugiu et al 2021). Parfenova et al (2016) have indicated that the impact of the tax policy of the state is vital for a country's economy.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis conducted by the European Commission (2019) on non-compliance among EU Member States (period 2001-2016 reveals that Slovenia is among the 14 Member States with the lowest estimated lost revenue regarding tax noncompliance (accounting for less than 5% of the EU-28 total). An additional integrative analysis on tax compliance by Surugiu et al (2021) utilized unbalanced panel data for the European Union (EU28), including Slovenian data, covering the period from 2007 to 2017. This analysis demonstrated a positive and significant influence of the quality of the education system on tax compliance, similar to findings in studies by Dayio glu Erul (2020) and Tilahun (2019).…”
Section: Introductionmentioning
confidence: 99%